2018
DOI: 10.3390/recycling3010007
|View full text |Cite
|
Sign up to set email alerts
|

Material Implications of Rural Electrification—A Methodological Framework to Assess In-Use Stocks of Off-Grid Solar Products and EEE in Rural Households in Bangladesh

Abstract: "Universal access to electricity" is proclaimed as the seventh sustainable development goal (SDG 7) of the United Nations (UN) Sustainable Development Goals list. The achievement of this goal will result in a rapid diffusion of energy technologies that would in turn increase materials stocks, subsequently increase the raw material demand as well as the arising waste flows. This study describes a methodological framework to assess in-use stocks of off-grid solar products and electrical and electronic equipment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Such compounds as ammonia, hydrogen cyanide, hydrogen chloride and hydrogen bromide were also analysed. It was observed that for most of the samples, HBr was not found in the exhaust gases (samples 1-5, 7-18) and no increases in HCl in the concentrations of 12 samples were observed (samples 1-7, 9,11,13,16,18).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Such compounds as ammonia, hydrogen cyanide, hydrogen chloride and hydrogen bromide were also analysed. It was observed that for most of the samples, HBr was not found in the exhaust gases (samples 1-5, 7-18) and no increases in HCl in the concentrations of 12 samples were observed (samples 1-7, 9,11,13,16,18).…”
Section: Resultsmentioning
confidence: 96%
“…It is estimated that the electrical and electronic equipment in use these days represents the greatest increase in waste volume with an annual growth of 4% [7][8][9]; on a global scale this corresponds to 20 to 50 mil tons of waste [10][11][12][13]. Europe produces around 12 mil tons of electronic waste (WEEE), which equals around 23 kg per person, Europe's population equals 505.7 mil [7].…”
Section: Introductionmentioning
confidence: 99%
“…Italy [24], the Netherlands [25], France [26], South Africa [27], Morocco [28], Tanzania [29], Malaysia [30],…”
Section: B Selection Of the Existingmentioning
confidence: 99%
“…In the current energy crisis, energy is considered to play as a key role in the achievement of good health, adequate social development and improved quality of life for people in developing countries in the world generally [1]. Both produced and consumed energy resources, especially renewable ones, in hydropower is particular have led to an increase in the demand for energy in many countries of the wourld [2].…”
Section: Introductionsmentioning
confidence: 99%